2013
DOI: 10.1371/journal.pone.0061212
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Bone Metastasis-Related MicroRNAs in Lung Adenocarcinoma by High-Throughput Sequencing

Abstract: BackgroundMicroRNAs (miRNAs) are a class of small noncoding RNAs that regulate gene expression at the post-transcriptional level. They participate in a wide variety of biological processes, including apoptosis, proliferation and metastasis. The aberrant expression of miRNAs has been found to play an important role in many cancers.ResultsTo understand the roles of miRNAs in the bone metastasis of lung adenocarcinoma, we constructed two small RNA libraries from blood of lung adenocarcinoma patients with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…A and B). We then removed genes with extremely low FPKM (FPKM < 0.5) values in both the T and C groups on that basis . Therefore, 22 upregulated and 73 downregulated DEGs were included after filtering (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…A and B). We then removed genes with extremely low FPKM (FPKM < 0.5) values in both the T and C groups on that basis . Therefore, 22 upregulated and 73 downregulated DEGs were included after filtering (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the correlation of dysregulation of miRNAs with LAD is increasingly reported. By high-throughput sequencing combined with differential expression analysis, Xie' et al identified that 7 microRNAs were down-regulated and 21 microRNAs were up-regulated in LAD with bone metastasis [10]. By performing microRNA expression profiles of whole blood in lung adenocarcinoma, Patnaik and his colleagues showed that four microRNAs (miR-190b, miR-630, miR-942, and miR-1284) were the most frequent constituents of the classifiers generated during the analyses, suggesting that whole blood microRNA expression profiles can be used to distinguish lung cancer cases from clinically relevant controls [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Xie and colleagues constructed and compared two sRNA libraries from the blood samples of patients with lung adenocarcinoma with and without bone metastasis [70]. The data showed that seven miRNAs were downregulated and 21 miRNAs were upregulated in lung adenocarcinoma with bone metastasis.…”
Section: • • Mirnas For the Detection Of Bone Metastasis From Breast mentioning
confidence: 99%